Effectiveness of an ergonomic intervention on the productivity of workers with upper-extremity disorders - a randomized controlled trial - Kari-Pekka Martimo; Rahman Shiri; Helena Miranda; Ritva Ketola; Helena Varonen; Eira Viikari-Juntura (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
OBJECTIVES: The aim of this study was to investigate the effectiveness of an ergonomic intervention on productivity loss at work caused by upper-extremity disorders (UED). METHODS: Workers with medically verified UED were invited to participate. The intervention consisted of a physician contacting the worker's supervisor and an occupational physiotherapist conducting an ergonomic assessment at the worksite. Before and after the intervention, the employees self-assessed UED-related productivity loss (ie, decreased quality and quantity of the daily work output). We tested for differences between groups at 8 and subsequently 12 weeks. We also applied generalized estimating equation (GEE) to analyze repeated measures data. RESULTS: Altogether 177 employees were randomized. The overall participation rate was 88%. At baseline, 54% of the intervention group and 58% of the control group reported productivity loss. The magnitude of productivity loss was 17% and 20%, respectively. At 8 weeks, both the proportion and magnitude of productivity loss were lower in the intervention than the control group, but the differences were statistically significant only at 12 weeks (proportion 25% versus 51%, magnitude 7% versus 18%, P=0.001 for both). Using GEE analyses, we also found the differences to be statistically significant (proportion 38% versus 52%, magnitude 12% versus 18%). The intervention only benefitted employees with 0-20% loss of productivity at baseline, not those with a higher initial productivity loss. CONCLUSIONS: Early ergonomic intervention, in addition to adequate medical care, is effective in preventing and restoring self-reported productivity loss associated with UED.